Glass plate with low radiation laminated film and glass product
The glass plate with a low-radiation stacked film, featuring a ZrO2 content layer with controlled roughness, addresses durability and antifouling issues, offering improved scratch resistance and heat insulation.
Patent Information
- Application Number
- JP2024181931
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-09-18
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-28
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing glass products with low-radiation films lack sufficient durability, scratch resistance, and surface antifouling properties, which are essential for improved performance in various applications.
A glass plate with a low-radiation stacked film is designed, featuring a transparent conductive layer sandwiched between a ZrO2 content layer, where ZrO2 content ranges from 8 to 100 mol% and has an average surface roughness of 12 nm or less, enhancing the durability and antifouling properties.
The glass plate exhibits improved scratch resistance, reduced surface fouling, and enhanced durability, while maintaining excellent heat insulation characteristics.
Smart Images

Figure 2025013861000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a glass sheet with a low emissivity laminated film and a glass product. [Background technology]
[0002] Depending on the application, a glass sheet is required to have thermal insulation properties. The thermal insulation properties of a glass sheet can be improved, for example, by forming a low-emissivity (Low-E) film on the surface of the glass sheet. The low-emissivity film typically includes a transparent conductive layer, and in some cases, further includes a SiO2 layer disposed on the transparent conductive layer (for example, Patent Documents 1 and 2).
[0003] The SiO2 layer can be produced, for example, by hydrolysis and condensation polymerization of a hydrolyzable silicon compound such as silicon alkoxide by the so-called sol-gel method. The SiO2 layer can also be produced, for example, by coating a glass plate with a mixture of an aqueous solution of sodium silicate and / or potassium silicate and an aqueous solution of lithium silicate, drying the resulting coating, and further heat-treating it. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2006 / 098285 [Patent Document 2] Special Publication No. 2014-514997 Summary of the Invention [Problem to be solved by the invention]
[0005] However, conventional glass sheets with a low-emissivity film have room for improvement in terms of properties required for glass products, such as durability, scratch resistance, and surface antifouling properties.
[0006] Therefore, an object of the present invention is to provide a glass sheet with a low emissivity laminated film having improved properties required for glass products. [Means for solving the problem]
[0007] As a result of intensive research, the inventors have found that the arithmetic mean roughness of the surface of a low-emissivity film affects the scratch resistance and surface antifouling properties. Based on this finding, the inventors have furthered their research and completed the present invention.
[0008] The present invention relates to A glass plate and A low emissivity laminate film supported on the glass plate; Equipped with The low-emissivity laminated film has a ZrO2-containing layer disposed on the outermost side of the low-emissivity laminated film, and a transparent conductive layer disposed between the glass plate and the ZrO2-containing layer, The ZrO2 content in the ZrO2-containing layer is 8 mol% or more and 100 mol% or less, The SiO2 content in the ZrO2-containing layer is 0 mol% or more and 92 mol% or less, The ZrO2-containing layer has a surface with an arithmetic mean roughness Ra of 12 nm or less, which is smaller than the surface with an arithmetic mean roughness Ra of the transparent conductive layer. Effect of the Invention
[0009] According to the present invention, it is possible to provide a glass sheet with a low emissivity laminated film having improved properties required for glass products. [Brief description of the drawings]
[0010] [Figure 1] 1 is a schematic cross-sectional view of a glass plate with a low emissivity laminated film according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged cross-sectional view showing the vicinity of the surface of a transparent conductive layer in a glass plate with a low-emissivity laminated film. [Diagram 3] FIG. 1 is a schematic cross-sectional view showing an example of a glass product. [Figure 4A]FIG. 1 is a diagram for explaining the temperature distribution of a conventional glass product placed in an environment where the outdoor temperature is lower than the indoor temperature. [Figure 4B] FIG. 4 is a diagram for explaining the temperature distribution of the glass product of FIG. 3 placed in an environment where the outdoor temperature is lower than the indoor temperature. [Diagram 5] FIG. 1 is a schematic cross-sectional view showing a glass product according to a first modified example. [Figure 6] FIG. 11 is a schematic cross-sectional view showing a glass product according to a second modified example. [Figure 7] FIG. 11 is a schematic cross-sectional view showing a glass product according to a third modified example. [Figure 8] FIG. 11 is a schematic cross-sectional view showing a glass product according to a fourth modified example. [Figure 9] FIG. 1 shows a glass product used as a skylight for transportation equipment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will now be described in detail, but the following description is not intended to limit the present invention to a specific embodiment.
[0012] <Embodiments of glass plate with low emissivity laminated film> As shown in Fig. 1, a glass plate 10 with a low-emissivity laminate film of this embodiment includes a glass plate 1 and a low-emissivity laminate film 2. The low-emissivity laminate film 2 is supported by the glass plate 1. The low-emissivity laminate film 2 is in contact with the glass plate 1, for example, and covers a main surface (the surface having the widest area) of the glass plate 1. The low-emissivity laminate film 2 is in contact with, for example, the external atmosphere (typically air).
[0013] The low emissivity laminated film 2 has a layer containing ZrO2 (ZrO2-containing layer 3) and a transparent conductive layer 4. The ZrO2-containing layer 3 is disposed on the outermost side of the low emissivity laminated film 2 and is in contact with the external atmosphere. The transparent conductive layer 4 is disposed between the glass plate 1 and the ZrO2-containing layer 3 and is in contact with, for example, the ZrO2-containing layer 3. The transparent conductive layer 4 may or may not be in contact with the glass plate 1.
[0014] In the glass plate 10 with the low-emissivity laminated film of this embodiment, the arithmetic mean roughness Ra of the surface (surface 3a on the external atmosphere side) of the ZrO2-containing layer 3 is 12 nm or less, which is smaller than the arithmetic mean roughness Ra of the surface of the transparent conductive layer 4 (surface 4a on the ZrO2-containing layer 3 side). The arithmetic mean roughness Ra of the surface 3a is preferably 10 nm or less, more preferably 8 nm or less, and particularly preferably 6 nm or less. The lower limit of the arithmetic mean roughness Ra of the surface 3a is not particularly limited, and is, for example, 1 nm. The arithmetic mean roughness Ra of the surface 3a can be specified by a method conforming to the provisions of JIS B0601:2013.
[0015] In the low-emissivity laminated glass plate 10, the arithmetic mean roughness Ra of the surface 4a of the transparent conductive layer 4 is not particularly limited as long as it is larger than the arithmetic mean roughness Ra of the surface 3a of the ZrO2-containing layer 3, and is, for example, 14 nm or more. The upper limit of the arithmetic mean roughness Ra of the surface 4a is not particularly limited, and may be 50 nm or 25 nm. The arithmetic mean roughness Ra of the surface 4a can be determined, for example, by the following method. First, the cross section of the low-emissivity laminated glass plate 10 is observed with a scanning electron microscope (SEM). FIG. 2 shows an example of an electron microscope image of the vicinity of the surface 4a of the transparent conductive layer 4 obtained by SEM observation. The roughness curve of the surface 4a is determined from the obtained electron microscope image. The arithmetic mean roughness Ra of the surface 4a can be determined from the obtained roughness curve by the calculation method specified in JIS B0601:2013. The arithmetic mean roughness Ra of the surface 4a may be determined by a method conforming to the provisions of JIS B0601:2013 in a state where the ZrO2-containing layer 3 is not formed (the surface 4a of the transparent conductive layer 4 is exposed to the outside). The surface 4a of the transparent conductive layer 4 may not be completely covered by the ZrO2-containing layer 3, and a part of it may be exposed to the outside. In this case, from the viewpoint of fully obtaining the effects of the present invention, it is preferable that the surface 3a of the ZrO2-containing layer 3 and the part of the surface 4a of the transparent conductive layer 4 exposed to the outside both have an arithmetic mean roughness Ra of 12 nm or less.
[0016] (Glass plate) The glass plate 1 may be a float glass plate or a figured glass plate. The surface of the float glass plate has excellent smoothness. The arithmetic mean roughness Ra of the surface of the float glass plate is preferably 1 nm or less, more preferably 0.5 nm or less.
[0017] The surface of the figured glass has macroscopic irregularities that can be seen by the naked eye. Macroscopic irregularities refer to irregularities with an average interval RSm on the order of millimeters. The average interval RSm means the average value of the interval of one period of peaks and valleys calculated from the points where the roughness curve intersects with the average line. Macroscopic irregularities can be seen when the evaluation length in the roughness curve is set to the order of centimeters. The average interval RSm of the irregularities on the surface of the figured glass may be 0.3 mm or more, 0.4 mm or more, or 0.45 mm or more. The average interval RSm may be 2.5 mm or less, 2.1 mm or less, 2.0 mm or less, or 1.5 mm or less. The irregularities on the surface of the figured glass plate preferably have an average interval RSm in the above range and a maximum height Rz of 0.5 μm to 10 μm, particularly 1 μm to 8 μm. The average interval RSm and the maximum height Rz are values specified in JIS B0601:2013. Even in the case of a molded glass, for example, in a surface roughness measurement in which the evaluation length in the roughness curve is several hundred nm, the arithmetic average roughness Ra may be several nm or less (for example, 1 nm or less). That is, the surface of the molded glass may have excellent smoothness microscopically. For example, an atomic force microscope (AFM) observation may be used as a surface roughness measurement in which the evaluation length is several hundred nm.
[0018] The composition of the glass plate 1 may be the same as that of conventional figured glass, architectural glass, automotive glass, etc. The content of iron oxide in the glass plate 1 may be 0.06 wt% or less or 0.02 wt% or less, calculated as Fe2O3. Iron oxide is a typical coloring component. When the glass plate 1 is colored glass, the content of iron oxide in the glass plate 1 may be 0.3 wt% or more and 1.5 wt% or less.
[0019] The thickness of the glass plate 1 is not particularly limited and is, for example, 0.5 mm to 15 mm.
[0020] (ZrO2 containing layer) The ZrO2-containing layer 3 contains ZrO2, and the content is 8 mol% or more and 100 mol% or less. The lower limit of the ZrO2 content in the ZrO2-containing layer is preferably 10 mol%. The upper limit of the ZrO2 content is preferably 80 mol%, more preferably 60 mol%, and further preferably 30 mol%. The ZrO2 content may be 23 mol% or more and 100 mol% or less, or 23 mol% or more and 72 mol% or less. In some cases, the ZrO2 content may be 10 mol% or more and 30 mol% or less, or 20 mol% or more and 30 mol% or less. The higher the ZrO2 content in the ZrO2-containing layer 3, the more the alkali resistance of the ZrO2-containing layer 3 tends to improve. On the other hand, if the ZrO2 content is too high, the refractive index of the ZrO2-containing layer 3 improves, and the visible light reflectance may become too high.
[0021] The ZrO2-containing layer 3 may further contain SiO2 as a component other than ZrO2. The content of SiO2 in the ZrO2-containing layer 3 is 0 mol% or more and 92 mol% or less, preferably 0 mol% or more and 77 mol% or less, and more preferably 28 mol% or more and 77 mol% or less.
[0022] The physical thickness of the ZrO2-containing layer 3 is, for example, 15 nm or more and 150 nm or less, and may be 20 nm or more or 30 nm or more, preferably 30 nm or more and 150 nm or less, and more preferably 50 nm or more and 120 nm or less. The ZrO2-containing layer 3 having such a physical thickness is suitable for suppressing a change in the reflected color tone caused by disposing the ZrO2-containing layer 3 on a laminate (a glass plate with a transparent conductive layer) including the transparent conductive layer 4 and the glass plate 1.
[0023] (Transparent conductive layer) A first example of the transparent conductive layer 4 is a layer substantially made of fluorine-containing tin oxide and having a thickness of 200 nm or more and 400 nm or less. In this specification, "substantially made of" means that the content of the component in the layer is 90 mol% or more, further 95 mol% or more, and particularly 99 mol% or more. The transparent conductive layer 4 of the first example preferably has a thickness of 300 nm or more and 400 nm or less. When the transparent conductive layer 4 of the first example is used, the underlayer 5 described later preferably has a two-layer structure (for example, the underlayer 5 of the second example). When the low emissivity laminated film 2 includes the transparent conductive layer 4 of the first example, the ZrO2-containing layer 3 preferably has a physical thickness of 10 nm or more and 100 nm or less.
[0024] A second example of the transparent conductive layer 4 is a layer substantially made of fluorine-containing tin oxide and having a thickness of 400 nm or more and 800 nm or less. The transparent conductive layer 4 of the second example preferably has a thickness of 500 nm or more and 700 nm or less. When the transparent conductive layer 4 of the second example is used, the underlayer 5 described below preferably has a two-layer structure (for example, the underlayer 5 of the second example). When the low emissivity laminated film 2 includes the transparent conductive layer 4 of the second example, the ZrO2-containing layer 3 preferably has a physical thickness of 40 nm or more and 250 nm or less.
[0025] A third example of the transparent conductive layer 4 includes a transparent conductive layer including a first transparent conductive layer substantially made of antimony-containing tin oxide and having a thickness of 100 nm or more and 300 nm or less, and a second transparent conductive layer substantially made of fluorine-containing tin oxide and having a thickness of 150 nm or more and 400 nm or less. The transparent conductive layer 4 of the third example may be made of a first transparent conductive layer and a second transparent conductive layer. In the third example, the first transparent conductive layer and the second transparent conductive layer are laminated in this order, for example, from the main surface side of the glass plate 1. In the transparent conductive layer 4 of the third example, the first transparent conductive layer preferably has a thickness of 150 nm or more and 200 nm or less. In the transparent conductive layer 4 of the third example, the second transparent conductive layer preferably has a thickness of 200 nm or more and 300 nm or less. When the transparent conductive layer 4 of the third example is used, the underlayer 5 described later preferably has a two-layer structure (for example, the underlayer 5 of the second example). When the low emissivity laminated film 2 includes the transparent conductive layer 4 of the third example, the ZrO2-containing layer 3 preferably has a physical thickness of 10 nm or more and 100 nm or less.
[0026] (base layer) The low emissivity laminated film 2 may further include an underlayer 5. The underlayer 5 is disposed, for example, between the glass plate 1 and the transparent conductive layer 4, and may be in direct contact with both the glass plate 1 and the transparent conductive layer 4.
[0027] A first example of the underlayer 5 is a layer containing silicon oxycarbide (SiOC) as a main component and having a thickness of 20 nm or more and 120 nm or less. In this specification, the "main component" means the component that is contained most abundantly on a molar basis. The underlayer 5 of the first example may be substantially composed of silicon oxycarbide. The underlayer 5 of the first example preferably has a thickness of 30 nm or more and 100 nm or less, and more preferably has a thickness of 30 nm or more and 60 nm or less.
[0028] A second example of the underlayer 5 includes an underlayer consisting of a first underlayer substantially made of tin oxide and having a thickness of 10 nm to 90 nm, and a second underlayer substantially made of SiO2 and having a thickness of 10 nm to 90 nm. In the second example, the first underlayer and the second underlayer are laminated in this order, for example, from the main surface side of the glass plate 1. In the underlayer 5 of the second example, the first underlayer preferably has a thickness of 10 nm to 70 nm, more preferably has a thickness of 12 nm to 40 nm. In the underlayer 5 of the second example, the second underlayer preferably has a thickness of 10 nm to 70 nm, more preferably has a thickness of 12 nm to 40 nm.
[0029] A third example of the underlayer 5 includes an underlayer consisting of a first underlayer substantially made of SiO2 and having a thickness of 10 nm to 30 nm, a second underlayer substantially made of tin oxide and having a thickness of 10 nm to 90 nm, and a third underlayer substantially made of SiO2 and having a thickness of 10 nm to 90 nm. In the third example, the first underlayer, the second underlayer, and the third underlayer are laminated in this order, for example, from the main surface side of the glass plate 1. In the underlayer 5 of the third example, the first underlayer preferably has a thickness of 10 nm to 20 nm. In the underlayer 5 of the third example, the second underlayer preferably has a thickness of 10 nm to 70 nm, more preferably a thickness of 12 nm to 40 nm. In the third example of the underlayer 5, the third underlayer preferably has a thickness of 10 nm or more and 70 nm or less, and more preferably has a thickness of 12 nm or more and 40 nm or less.
[0030] (Other low-emissivity films) The glass plate 10 with a low-emissivity laminate film of this embodiment may further include another low-emissivity film arranged on the surface of the glass plate 1 opposite to the surface on the low-emissivity laminate film 2 side. The other low-emissivity film is, for example, a film including a laminate in which a dielectric layer, a layer containing Ag as a main component, and another dielectric layer are laminated in this order.
[0031] (Method of manufacturing glass sheet with low-emissivity laminated film) The glass plate 10 with the low emissivity laminated film of this embodiment can be produced, for example, by forming a ZrO2-containing layer 3 on the transparent conductive layer 4 in a laminate (glass plate with a transparent conductive layer) including the transparent conductive layer 4 and the glass plate 1. As the glass plate with a transparent conductive layer, a commercially available product can be used. The ZrO2-containing layer 3 can be produced, for example, by the following method. First, a coating liquid for forming the ZrO2-containing layer 3 is applied onto the transparent conductive layer 4 to produce a liquid film.
[0032] The coating liquid contains, for example, a precursor of ZrO2 and an organic solvent. The precursor of ZrO2 contains, for example, at least one selected from the group consisting of zirconium oxychloride and zirconium oxynitrate, and preferably contains zirconium oxynitrate.
[0033] The organic solvent contained in the coating liquid is not particularly limited as long as it can dissolve the ZrO2 precursor or can be uniformly mixed with the aqueous solution of the ZrO2 precursor. The organic solvent preferably contains an alcohol having 1 to 5 carbon atoms. The number of hydroxyl groups contained in this alcohol is, for example, 1 to 3. This alcohol may be a primary alcohol or a secondary alcohol. This alcohol may further contain a functional group other than the hydroxyl group (for example, an ether group). Examples of the alcohol having 1 to 5 carbon atoms include methanol, ethanol, propanol, butanol, propylene glycol, propylene glycol monomethyl ether (PGME), and 3-methoxy-1-butanol. The organic solvent may contain alcohols other than the alcohol having 1 to 5 carbon atoms.
[0034] The coating liquid may further contain silicon alkoxide and / or its hydrolysis product. Silicon alkoxide is, for example, a compound represented by the general formula Si(OR) n X 4-nThe formula is represented by the formula: n is an integer of 1 to 4, preferably an integer of 2 to 4. OR is each independently an alkoxy group having 1 to 4 carbon atoms. Examples of the alkoxy group having 1 to 4 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, and a butoxy group. X represents a functional group that does not have hydrolysis. Each X may be independently a hydrocarbon group having 1 to 6 carbon atoms. Examples of the hydrocarbon group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a pentyl group, and a phenyl group. Examples of silicon alkoxides include tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, methyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, diethyldiethoxysilane, and phenyltriethoxysilane.
[0035] When the coating liquid contains silicon alkoxide, it is preferable that the coating liquid further contains water and a catalyst. The amount of water in the coating liquid is preferably 1 to 40 equivalents, more preferably 1 to 10 equivalents, and even more preferably 2 to 5 equivalents, based on the number of moles of water required for hydrolysis of the silicon alkoxide.
[0036] The catalyst is not particularly limited as long as it functions as a hydrolysis catalyst. The hydrolysis catalyst may be a base, but is preferably an acid. The acid may be an inorganic acid or an organic acid. The boiling point of the acid is preferably 300° C. or lower. Examples of the acid include hydrochloric acid and nitric acid. The content of the acid in the coating liquid is, for example, 0.001 wt % to 0.3 wt %, preferably 0.001 wt % to 0.03 wt %, and more preferably 0.002 wt % to 0.02 wt %.
[0037] The solid content of the coating liquid is, for example, 0.1 wt% to 7 wt%, preferably 6 wt% or less, more preferably 5 wt% or less, further preferably 4 wt% or less, and particularly preferably 3 wt% or less. The lower limit of the solid content of the coating liquid is, for example, 0.5 wt%.
[0038] The method for applying the coating liquid to the glass plate with a transparent conductive layer is not particularly limited, but examples thereof include spray coating, flow coating, roll coating, spin coating, slot die coating, and bar coating.
[0039] The thickness of the liquid film obtained by applying the coating liquid to the glass plate with a transparent conductive layer is not particularly limited, and is, for example, several μm to several tens of μm.
[0040] Next, the liquid film is dried and further fired to obtain a ZrO2-containing layer 3. The drying step is performed by heating the liquid film at a temperature of 100°C or more and 500°C or less for a time of 2 seconds to 10 minutes. In the firing step, the maximum temperature reached by the glass sheet with a transparent conductive layer is, for example, 800°C or less. In the firing step, the time during which the temperature of the glass sheet with a transparent conductive layer is 400°C or more is preferably 2 seconds or more. The firing step may also serve as a drying step. Furthermore, the firing step may also serve as a step of hot-forming the glass sheet 1, or a step of heating the glass sheet 1 for air-cooling and tempering.
[0041] The drying step and the firing step are carried out, for example, by hot air drying. The drying step and the firing step may be carried out by holding the glass plate with the transparent conductive layer, on which the liquid film has been formed, in a heating furnace set at a predetermined temperature for a predetermined time.
[0042] The manufacturing method of the low-emissivity laminated glass plate 10 is not limited to the above-mentioned method. For example, the low-emissivity laminated glass plate 10 can be manufactured by providing a ZrO2-containing layer 3 on a glass plate with a transparent conductive layer using an online CVD method.
[0043] (Characteristics of glass sheets with low-emissivity laminated film) In the glass plate 10 with the low-emissivity laminated film of this embodiment, the arithmetic mean roughness Ra of the surface 3a of the ZrO2-containing layer 3 is 12 nm or less. Such a surface 3a is resistant to scratches even when rubbed against a solid object, and has excellent scratch resistance. Furthermore, the surface 3a is resistant to oily matters such as fingerprints, and has excellent surface antifouling properties. The glass plate 10 with the low-emissivity laminated film of this embodiment also has excellent heat insulation properties.
[0044] Furthermore, the glass plate 10 with the low-emissivity laminated film is excellent in durability, particularly in alkali resistance. The alkali resistance can be evaluated, for example, by the following method. First, a durability test is performed on the glass plate 10 with the low-emissivity laminated film. In the durability test, an aqueous sodium hydroxide solution with a concentration of 1N (1 mol / L) and a temperature of 23°C is prepared. The durability test is performed by immersing the glass plate 10 with the low-emissivity laminated film in the aqueous sodium hydroxide solution for 24 hours. Next, the L1 of the reflected light from the ZrO2-containing layer 3 on the glass plate 10 with the low-emissivity laminated film after the durability test is measured using a spectrophotometer. * Value, a1 * Value and b1 * Measure the value. L1 * Value, a1 * Value and b1 * The value is L * a * b * Based on the CIE1976 color system. The obtained L1 * Value, a1 * Value and b1 * value and L0 of reflected light from the ZrO2-containing layer 3 in the glass plate 10 with the low emissivity laminated film before the durability test. * Value, a0 * Value and b0 * The change in color of reflected light, ΔE, is calculated based on the * The alkali resistance can be evaluated by ΔE * can be calculated by the following formulas (1) to (4). ΔL * =L0 * -L1 * (1) Δa * =a0 * -a1 * (2) Δb * =b0 * -b1 * (3) ΔE * = {(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 (4)
[0045] For the low-emissivity laminated glass sheet 10, ΔE calculated from the above test results * is, for example, 5 or less, preferably 4 or less, more preferably 3 or less, even more preferably 2 or less, particularly preferably 1.5 or less, particularly preferably 1 or less, and in some cases may be 0.5 or less. * The lower limit is not particularly limited, and is, for example, 0.05.
[0046] The visible light reflectance of the low-emissivity laminated glass plate 10 is not particularly limited, and is, for example, 15% or less, preferably 10% or less, more preferably 8% or less, and further preferably 7% or less. The lower limit of the visible light reflectance of the low-emissivity laminated glass plate 10 is, for example, 1%. In this specification, the visible light reflectance is a value determined by the provisions of JIS R3106:1998, and the specific measurement conditions are described in the Examples section.
[0047] <Embodiments of Glass Products> FIG. 3 shows an example of a glass product 100 used as a skylight for a building. The glass product 100 comprises a glass plate 10 with a low-emissivity laminate film and a second glass plate 15 facing the glass plate 10 with a low-emissivity laminate film via an air gap layer 30. In this specification, the glass plate 1 of the glass plate 10 with a low-emissivity laminate film may be referred to as the "first glass plate" in comparison with the second glass plate 15 provided in the glass product. The glass product 100 may further comprise a low-emissivity film 25 (first low-emissivity film) supported by the second glass plate 15 and in contact with the air gap layer 30. The glass product 100 in FIG. 3 is a double-glazing unit.
[0048] The glass product 100 is incorporated into a window structure of a building either alone as a glass unit or as a window assembly with a window frame (sash) portion, and separates an indoor space from an outdoor space. The glass sheet 10 with a low-emissivity laminated film is located closest to the outdoor space, and the low-emissivity laminated film 2 is in contact with the outdoor space. The second glass sheet 15 is located closest to the indoor space, and in contact with the indoor space.
[0049] In the field of double-glazing units, as a customary practice for those skilled in the art, the main surfaces of the glass sheets of the unit are numbered in the order of the first surface, the second surface, the third surface, and so on, starting from the outdoor space side. Based on this customary practice, in the glass product 100 shown in FIG. 3, the main surface 1a of the first glass sheet 1 opposite the gap layer 30 (the main surface facing the outdoor space) is the first surface (#1 surface), the main surface 1b of the first glass sheet 1 facing the gap layer 30 is the second surface (#2 surface), the main surface 15a of the second glass sheet 15 facing the gap layer 30 is the third surface (#3 surface), and the main surface 15b of the second glass sheet 15 opposite the gap layer 30 (the main surface facing the indoor space) is the fourth surface (#4 surface). In the glass product 100, the low-emissivity laminated film 2 is formed on the #1 surface, and the low-emissivity film 25 is formed on the #3 surface.
[0050] In the glass product 100, the second glass plate 15 may be the same as the first glass plate 1, as described above for the first glass plate 1.
[0051] The low-emissivity film 25 is not particularly limited, and a known film can be used. One example of the low-emissivity film 25 is a film containing a metal layer such as an Ag layer. This film has a structure (first laminated structure) in which, for example, a dielectric layer / metal layer / sacrificial layer / dielectric layer are laminated in this order from the main surface side of the second glass plate 15. The low-emissivity film 25 may have two or more metal layers. The low-emissivity film 25 having two or more metal layers is suitable for reducing the U value (coefficient of thermal transmission). The low-emissivity film 25 having two or more metal layers has a structure (second laminated structure) in which, for example, a dielectric layer / metal layer / sacrificial layer / dielectric layer / metal layer / sacrificial layer / dielectric layer are laminated in this order from the main surface side of the second glass plate 15. In the second laminated structure, the dielectric layer sandwiched between the sacrificial layer and the metal layer is shared by the two first laminated structures. In this way, the low-emissivity film 25 may have two or more first laminated structures.
[0052] Each of the dielectric layer, the metal layer, and the sacrificial layer may be a single layer made of one material, or may be a laminate of two or more layers made of different materials.
[0053] In the first laminated structure, the pair of dielectric layers sandwiching the metal layer and the sacrificial layer may be made of the same material or may be made of different materials.
[0054] A low-emissivity film 25 including metal layers is usually composed of 2n+1 or more layers, since if the number of metal layers is n, then the number of dielectric layers sandwiching the metal layers is n+1 or more.
[0055] The metal layer is, for example, an Ag layer. The Ag layer may be a layer containing Ag as a main component, and may be a layer substantially made of Ag. The metal layer may contain a material in which Ag is doped with a metal such as palladium, gold, indium, zinc, tin, aluminum, or copper. The low-emissivity film 25 may have one Ag layer, or may have two or three or more Ag layers.
[0056] The total thickness of the metal layers in the low-emission film 25 is, for example, 18 to 34 nm, and preferably 22 to 29 nm.
[0057] The sacrificial layer is, for example, a layer containing at least one selected from titanium, zinc, nickel, chromium, zinc / aluminum alloy, niobium, stainless steel, alloys thereof, and oxides thereof as a main component, and is preferably a layer containing at least one selected from titanium, titanium oxide, zinc, and zinc oxide as a main component. The thickness of the sacrificial layer is, for example, 0.1 to 5 nm, and preferably 0.5 to 3 nm.
[0058] The dielectric layer is, for example, a layer containing an oxide or nitride as a main component, and a more specific example of such a dielectric layer is a layer containing at least one selected from the oxides and nitrides of silicon, aluminum, zinc, tin, titanium, indium, and niobium as a main component. The thickness of the dielectric layer is, for example, 8 to 120 nm, and preferably 15 to 85 nm.
[0059] The method of forming the metal layer, the sacrificial layer, and the dielectric layer is not particularly limited, and known thin film formation methods can be used. For example, these layers can be formed by a sputtering method. The dielectric layer composed of an oxide or a nitride can be formed by, for example, reactive sputtering, which is a type of sputtering method. The sacrificial layer is a layer necessary for forming a dielectric layer on a metal layer by reactive sputtering (a layer that prevents oxidation of the metal layer by oxidizing itself during reactive sputtering), and the name of the sacrificial layer is well known to those skilled in the art.
[0060] The glass product 100 may further include a second low-emissivity film (not shown) supported by the second glass plate 15 and in contact with the indoor space. The second low-emissivity film may be the same as the low-emissivity film 2, or may be the same as the low-emissivity film 2.
[0061] The thickness of the gap layer 30 is maintained by a spacer 40 arranged on the periphery (periphery of the main surface facing the gap layer 30) of a pair of glass plates (first and second glass plates 1, 15) that sandwich the gap layer 30. The space in the gap layer 30 is sealed by a sealing material 45 arranged on the outer periphery of the spacer 40. An additional sealing material may be arranged between the spacer 40 and the glass plates 1, 15. A known configuration can be applied to the spacer 40 and the sealing material 45. For example, air (dry air) or an inert gas such as argon or krypton is introduced and filled into the gap layer 30. From the viewpoint of designing the U value of the glass product 100 to be smaller, the gas filled in the gap layer 30 is preferably argon or krypton, and more preferably krypton. In this specification, the gap layer 30 filled with air may be called an "air layer". The inside of the gap layer 30 may be reduced in pressure or may be a vacuum (pressure of about 10 Pa or less).
[0062] The thickness of the gap layer 30 is, for example, 4 to 16 mm, and preferably 6 to 16 mm. When the inside of the gap layer 30 is in a reduced pressure or vacuum state, the thickness of the gap layer 30 may be 0.3 to 1 mm.
[0063] The thickness of the glass product 100 is, for example, 10 to 22 mm, and may be 12 to 22 mm. When the inside of the gap layer 30 is in a reduced pressure or vacuum state, the thickness of the glass product 100 may be 5 to 15 mm.
[0064] In the glass product 100, the low-emissivity laminated film 2 is formed on the #1 surface, so that even if the outdoor temperature is lower than the indoor temperature, the drop in the temperature of the #1 surface can be suppressed. For example, a glass product having a low-emissivity film formed on the #2 surface is known in the past. In the glass product 150 of FIG. 4A, the low-emissivity laminated film 2 is not formed on the #1 surface, and the low-emissivity film 25 is formed on the #2 surface instead of the #3 surface. Except for the above, the structure of the glass product 150 is the same as that of the glass product 100. In FIG. 4A, the configurations of the spacer 40 and the sealing material 45 are omitted. When the glass product 150 is placed in an environment where there is not enough solar radiation and the outdoor temperature is lower than the indoor temperature, for example, an early morning environment, heat (far infrared rays) moves from the indoor to the outdoor in the glass product 150. The low-emissivity film 25 of the glass product 150 reflects this heat and returns it to the indoor. As a result, the first glass plate 1 located on the outdoor side is not supplied with enough heat, and the temperature of the #1 surface drops. #1 Condensation (for example, morning dew) occurs when the temperature of a surface drops below the dew point of the outdoor air.
[0065] In contrast, as shown in FIG. 4B, in the glass product 100, heat from the indoor side moves inside the first glass plate 1 and is reflected by the low emissivity laminated film 2. The heat reflected by the low emissivity laminated film 2 moves again inside the first glass plate 1 and is returned indoors. As a result, heat from indoors is sufficiently supplied to the first glass plate 1, and a decrease in temperature of the #1 surface is suppressed. When a decrease in temperature of the #1 surface is suppressed, a decrease in temperature of the low emissivity laminated film 2 formed on the #1 surface is also suppressed. In the glass product 100, the temperature of the outdoor-side surface of the low emissivity laminated film 2 is prevented from decreasing below the dew point of the outdoor air, so that condensation on the surface tends to be suppressed. If condensation is suppressed, visibility through the glass product 100 can be maintained in a good state.
[0066] The glass product 100 may be used in window structures other than skylights in buildings, and may also be used in window structures for transportation equipment, which will be described later.
[0067] <Glass product modification example 1> The application of the glass product including the glass plate 10 with the low emissivity laminated film of the present invention is not limited to a skylight for a building. In the first modification, the glass product is used as a normal window provided in the wall of a building. In detail, the glass product of the first modification is incorporated into the window structure of a building to separate an indoor space from an outdoor space.
[0068] In the glass product of the first modification, the glass plate 10 with a low-emissivity laminated film may be used alone. In this case, the structure of the glass product is, for example, the same as the structure of the glass product 300 of the fourth modification described below. This glass product is preferably used such that the low-emissivity laminated film 2 is located on the indoor space side. In other words, it is preferable that the low-emissivity laminated film 2 is formed on the main surface of the glass plate 1 on the indoor space side.
[0069] The glass product of the first modification may be a laminated glass in which the glass plate 10 with the low-emissivity laminate film is laminated to another glass plate via an interlayer film. In this case, the structure of the glass product is, for example, the same as the structure of the glass product 200 of the third modification described below. This glass product is preferably used so that the low-emissivity laminate film 2 is exposed on the indoor space side. In other words, it is preferable that the glass plate 10 with the low-emissivity laminate film is located closest to the indoor space side, and the low-emissivity laminate film 2 is formed on the main surface of the glass plate 1 on the indoor space side.
[0070] The glass product of the first modification may be a double-glazing unit in which the glass plate 10 with the low-emissivity laminated film is held facing another glass plate through a gap layer. FIG. 5 shows a glass product 110 of the first modification, which is a double-glazing unit. The glass product 110 includes the glass plate 10 with the low-emissivity laminated film and a second glass plate 15 facing the glass plate 10 with the low-emissivity laminated film through a gap layer 30. In the glass product 110, the glass plate 10 with the low-emissivity laminated film is located closest to the indoor space, and the low-emissivity laminated film 2 is in contact with the indoor space. The second glass plate 15 is located closest to the outdoor space, and in contact with the outdoor space. The glass product 110 does not include a low-emissivity film 25 supported by the second glass plate 15. Except for the above, the structure of the glass product 110 of this embodiment is the same as the structure of the glass product 100. Therefore, the same reference symbols are used for elements common to the glass product 100 and the glass product 110 of this embodiment, and their explanations may be omitted.
[0071] When the main surfaces of the glass plates of the glass product 110 are numbered in order from the outdoor space side as the first surface, the second surface, the third surface, and so on, in the glass product 110 shown in Fig. 5, the main surface 15a of the second glass plate 15 opposite the gap layer 30 (the main surface on the outdoor space side) is the first surface (#1 surface), the main surface 15b of the second glass plate 15 facing the gap layer 30 is the second surface (#2 surface), the main surface 1a of the first glass plate 1 facing the gap layer 30 is the third surface (#3 surface), and the main surface 1b of the first glass plate 1 opposite the gap layer 30 (the main surface on the indoor space side) is the fourth surface (#4 surface). In the glass product 110, the low emissivity laminated film 2 is formed on the #4 surface.
[0072] In the glass product 110, the second glass plate 15 may be the same as the first glass plate 1, as described above for the first glass plate 1.
[0073] When the glass product 110 is used, the glass plate 10 with the low emissivity laminated film is suitable for reflecting heat that would otherwise be lost in the form of infrared rays from an indoor space to an outdoor space. In other words, the glass product 110 is suitable for increasing the heat insulating performance from an indoor space to an outdoor space.
[0074] <Glass product modification example 2> In a second variant, the glass product is used as a door for a refrigerator or freezer. In detail, the glass product of variant 2 is incorporated into the door structure of a refrigerator or freezer to separate the interior space from the exterior space.
[0075] The glass product of the second modification is preferably a double-glazing unit in which the glass plate 10 with the low-emissivity laminate film is held facing another glass plate through an air gap layer. FIG. 6 shows a glass product 120 of the second modification, which is a double-glazing unit. The glass product 120 includes the glass plate 10 with the low-emissivity laminate film and a second glass plate 15 facing the glass plate 10 with the low-emissivity laminate film through an air gap layer 30. In the glass product 120, the glass plate 10 with the low-emissivity laminate film is located closest to the outside space, and the low-emissivity laminate film 2 is in contact with the outside space. The second glass plate 15 is located closest to the inside space, and is in contact with the inside space. Except for the above, the structure of the glass product 120 of this embodiment is the same as the structure of the glass product 110.
[0076] When the main surfaces of the glass plates of the glass product 120 are numbered in order from the outside-chamber space side as the first surface, the second surface, the third surface, and so on, in the glass product 120 shown in Fig. 6, the main surface 1a of the first glass plate 1 opposite the gap layer 30 (the main surface on the outside-chamber space side) is the first surface (#1 surface), the main surface 1b of the first glass plate 1 facing the gap layer 30 is the second surface (#2 surface), the main surface 15a of the second glass plate 15 facing the gap layer 30 is the third surface (#3 surface), and the main surface 15b of the second glass plate 15 opposite the gap layer 30 (the main surface on the inside-chamber space side) is the fourth surface (#4 surface). In the glass product 120, the low emissivity laminated film 2 is formed on the #1 surface.
[0077] In the glass product 120, the second glass plate 15 may be the same as the first glass plate 1, as described above for the first glass plate 1.
[0078] <Glass product modification example 3> In a third variant, the glass product is used as a skylight for transportation equipment. FIG. 7 shows a glass product 200 of variant 3. Examples of transportation equipment include vehicles, aircraft, and ships. Examples of vehicles include railroad cars and automobiles. The transportation equipment is typically an automobile. The glass product 200 comprises a glass sheet 10 with a low-emissivity laminated film, and further comprises, for example, a second glass sheet 15. The glass product 200 may further comprise an interlayer 50 disposed between the first glass sheet 1 and the second glass sheet 15. The glass product 200 in FIG. 7 is a laminated glass.
[0079] The glass product 200 is incorporated into a window structure of a transportation vehicle to separate the interior space from the exterior space. The glass plate 10 with low-emissivity laminated film is located closest to the interior space, and the low-emissivity laminated film 2 is in contact with the interior space. The second glass plate 15 is located closest to the exterior space, and in contact with the exterior space.
[0080] 7, the main surface of the second glass plate 15 opposite the interlayer 50 (the main surface 15a facing the outside space) is the first surface (#1 surface), the main surface 15b facing the interlayer 50 of the second glass plate 15 is the second surface (#2 surface), the main surface 1a facing the interlayer 50 of the first glass plate 1 is the third surface (#3 surface), and the main surface 1b facing the interlayer 50 of the first glass plate 1 is the fourth surface (#4 surface). In the glass product 200, the low emissivity laminated film 2 is formed on the #4 surface.
[0081] In the glass product 200, the second glass plate 15 may be the same as the first glass plate 1, as described above for the first glass plate 1.
[0082] A known material can be used as the intermediate film 50. The intermediate film 50 includes, for example, a polyvinyl acetal resin and a plasticizer. The polyvinyl acetal resin is not particularly limited, and for example, a polyvinyl butyral (PVB) resin can be used. The plasticizer is not particularly limited, and for example, triethylene glycol di(2-ethylhexanoate), triethylene glycol di(2-ethylbutyrate), tetraethylene glycol di(2-ethylbutyrate), tetraethylene glycol di(2-ethylhexanoate), etc. can be used.
[0083] The glass product 200 may further include a low-emissivity film (not shown) supported by the second glass plate 15 and in contact with the outside space. The low-emissivity film may be the same as the low-emissivity laminated film 2, or may be the same as the low-emissivity laminated film 2.
[0084] When the glass product 200 is in use, the glass plate 10 with the low emissivity laminated film is suitable for blocking heat by reflecting infrared light contained in solar radiation from the outside space side. In other words, the glass product 200 is suitable for suppressing an increase in temperature in the inside space of the aircraft.
[0085] The glass product 200 may be used in window structures other than skylights for transportation equipment, and may also be used in window structures for buildings.
[0086] <Glass product modification example 4> 8 is a schematic cross-sectional view of a glass product 300 of Modification 4. The glass product 300 has the same structure as the glass product 200, except that the glass product 300 does not include the second glass plate 15 and the interlayer film 50.
[0087] Like the glass product 200, the glass product 300 is incorporated into a window structure of a transportation device to separate the interior space from the exterior space. In the glass product 300, the main surface 1a of the glass plate 1 facing the exterior space is the first surface (#1 surface), and the main surface 1b of the glass plate 1 facing the interior space is the second surface (#2 surface). The low emissivity laminated film 2 is formed on the #2 surface.
[0088] In the glass product 300, the glass plate 10 with the low-emissivity laminated film may further have a compressive stress layer (not shown) formed on both main surfaces of the glass plate 1. That is, in the glass product 300, the glass plate 1 may be a tempered glass plate. The compressive stress layer can be formed by subjecting the glass plate 1 to a tempering treatment such as air-cooling tempering (thermal tempering). Air-cooling tempering is a well-known treatment for improving the strength of a glass plate by heating the glass plate, then blowing gas onto the surface of the glass plate to rapidly cool it, thereby forming a compressive stress layer on the surface. The heating temperature of the glass plate is typically equal to or higher than the strain point and equal to or lower than the softening point of the glass composition constituting the glass plate.
[0089] The glass product 300 is suitable for suppressing an increase in temperature in the cabin space, similar to the glass product 200. The glass product 300 may be used in window structures other than skylights for transportation equipment, and may also be used in window structures for buildings.
[0090] <Embodiment of transport equipment> FIG. 9 shows an example of a transportation equipment 500 equipped with a glass product 200 (or 300) as a skylight. The transportation equipment 500 in FIG. 9 is an automobile. A substantially rectangular sunroof opening 502 that communicates between the outside of the vehicle (outside the vehicle) and the inside of the vehicle (inside the vehicle) is formed in a roof 501 of the transportation equipment 500. An opening / closing mechanism (not shown) is provided on the edge of the sunroof opening 502, and the glass product 200 is supported by this opening / closing mechanism. The opening / closing mechanism has, for example, a guide rail, a slider, and an actuator. The guide rails are provided on the left and right edges of the sunroof opening 502, and extend in the direction in which the transportation equipment 500 advances. The slider supports the glass product 200 and can slide along the guide rail. The actuator can move the slider along the guide rail. The sunroof opening 502 can be opened and closed by moving the glass product 200 by the opening / closing mechanism. In detail, the glass product 200 is moved by the opening / closing mechanism between a closed position in which it fits into the sunroof opening 502 and an open position in which it is positioned outside and rearward of the transportation vehicle 500 with respect to the sunroof opening 502 . EXAMPLES
[0091] The present invention will be described in further detail below with reference to examples and comparative examples.
[0092] Example 1 [Glass plate with transparent conductive layer] First, a glass plate with a transparent conductive layer (Low-E glass manufactured by Nippon Sheet Glass Co., Ltd.) was cut out so that its main surface had a square shape with sides of 10 cm, and then cleaned. This glass plate with a transparent conductive layer had a SnO2 layer (first underlayer) with a physical thickness of 25 nm, a SiO2 layer (second underlayer) with a physical thickness of 25 nm, and a SnO2:F layer (transparent conductive layer) with a physical thickness of 340 nm laminated in this order on one main surface of a 3 mm thick float glass plate.
[0093] [Preparation of coating liquid] Next, 5.2g of tetraethoxysilane (ethyl orthosilicate), 7.99g of ethanol, 1.66g of purified water, and 0.15g of nitric acid with a concentration of 1N (1mol / L) were mixed. The resulting mixture was aged at 40°C for 8 hours to obtain 15g of a liquid containing a hydrolysis product of tetraethoxysilane. Next, 1.22g of this liquid, 4.67g of ethanol, and 0.11g of zirconium oxynitrate dihydrate (manufactured by Daiichi Kigenso Kagaku Kogyo, trade name "Zircosol ZN", 25wt% aqueous solution) were mixed to obtain 6g of a coating liquid. The solid content concentration in the coating liquid was 2.5wt%.
[0094] [Application of coating liquid] Next, the coating liquid was applied to the glass plate with the transparent conductive layer by the spin coating method. The spin coating method was carried out in the following manner. First, the glass plate with the transparent conductive layer was set at the center of the rotating table of the spin coater, and the glass plate with the transparent conductive layer was rotated. After the rotation speed was stabilized at 1000 rpm, 1.5 g of the prepared coating liquid was dropped onto the center of the glass plate with the transparent conductive layer using a Komagome pipette. At this time, the excess coating liquid was splashed from the peripheral portion of the glass plate with the transparent conductive layer. After confirming that the coating liquid had stopped splashing, the rotation of the glass plate with the transparent conductive layer was stopped.
[0095] [Drying] Next, the liquid film obtained by applying the coating liquid was dried. The liquid film was dried by transporting the glass plate with the transparent conductive layer on which the liquid film was formed into a tunnel-type transport furnace. The temperature set in the transport furnace was 300°C, and the length of the heating zone of the transport furnace was 1.6 m. The glass plate with the transparent conductive layer was transported at a transport speed of 0.8 m / min and heated for 2 minutes.
[0096] [Firing] Next, the obtained dried film was fired to prepare a ZrO2-containing layer. The firing was performed by holding the glass plate with the transparent conductive layer in an electric furnace set at 760°C for 4 minutes and 45 seconds. At this time, the maximum temperature reached by the glass plate with the transparent conductive layer was 650°C. In this way, the glass plate with the low emissivity laminated film of Example 1 was obtained.
[0097] (Examples 2 to 7, Comparative Examples 1 and 2) Glass plates with low-emissivity laminated film of Examples 2 to 7 and Comparative Examples 1 and 2 were obtained in the same manner as in Example 1, except that the composition of the coating liquid was adjusted so that the ZrO2 content in the ZrO2-containing layer and the solid concentration in the coating liquid were the values shown in Table 1.
[0098] Comparative Example 3 Except for not forming a ZrO2-containing layer, a glass plate with a low-emissivity laminate film of Comparative Example 3 was obtained by the same method as in Example 1. The glass plate with a low-emissivity laminate film of Comparative Example 3 had the same structure as the glass plate with a transparent conductive layer used in Example 1.
[0099] (Evaluation of glass sheets with low-emissivity laminated film) Next, the glass plates with the low emissivity laminated film of Examples 1 to 7 and Comparative Examples 1 to 3 were evaluated by the following methods.
[0100] [Physical thickness] The physical thickness of the ZrO2-containing layer was measured by the following method. First, the glass plate with the low-emissivity laminated film was cut, and the cross section was observed with a scanning electron microscope (S-4700 manufactured by Hitachi High-Technologies Corporation). The physical thickness of the ZrO2-containing layer was determined from the obtained electron microscope image.
[0101] [Optical properties] The optical properties of the glass plate with the low emissivity laminated film were evaluated by the following method. First, the spectral transmittance spectrum and the spectral reflectance spectrum of the glass plate with the low emissivity laminated film were measured using a spectrophotometer (U-4100 model, manufactured by Hitachi, Ltd.). The surface of the ZrO2-containing layer (or the transparent conductive layer) was used as the measurement surface, and absolute reflection measurements were performed at a reflection angle of 5° for the spectral reflectance spectrum. From the obtained spectrum, the visible light transmittance and visible light reflectance for the D65 light source defined in JIS R3106:1998 were calculated. Furthermore, under the measurement conditions for the spectral reflectance spectrum, the L0 of the reflected light from the ZrO2-containing layer was measured. * Value, a0 * Value and b0 * The L0 value was measured. * Value, a0 * Value and b0 * The value is L * a * b * It is based on the CIE1976 color system.
[0102] [Surface antifouling] The surface antifouling properties of the glass plate with the low-emissivity laminated film were evaluated by the following method. First, a rubber plate with a diameter of 15 mm was pressed against gauze soaked in oleic acid to adhere the oleic acid to the rubber plate. Next, the rubber plate was applied to the surface of the ZrO2-containing layer (or transparent conductive layer) at a rate of 100 g / cm2. 2 The oleic acid was attached to the surface by pressing the surface with a pressure of 25 g / cm2 for 10 seconds. Next, a cotton cloth moistened with purified water was placed on the surface with a pressure of 25 g / cm2. 2 The oleic acid was wiped off by moving the wipe back and forth 10 times at a pressure of 0.01 mm. Next, breath was blown onto the surface, and the presence or absence of traces of oleic acid was confirmed visually. If no traces of oleic acid were found, the surface antifouling property was evaluated as good (◯). If traces of oleic acid were found, the surface antifouling property was evaluated as poor (×).
[0103] [Scratch resistance] The scratch resistance of the glass plate with the low-emissivity laminated film was evaluated by the following method. First, the side of a 100-yen coin (an alloy of 75% copper and 25% nickel) was brought into contact with the surface of the ZrO2-containing layer so that the surface of the coin was perpendicular to the surface of the ZrO2-containing layer (or the transparent conductive layer). Next, the surface of the ZrO2-containing layer was rubbed with the coin by moving the coin 10 mm in the thickness direction of the coin while applying a load of 50 g. When the coin mark could not be visually confirmed on the surface of the ZrO2-containing layer, the scratch resistance was evaluated as good (◯). When the coin mark could be visually confirmed but was unclear, the scratch resistance was evaluated as insufficient (△). When the coin mark could be clearly confirmed by visual inspection, the scratch resistance was evaluated as poor (×).
[0104] [Durability] The durability (alkali resistance) of the glass plate with the low-emissivity laminated film was evaluated by the following method. First, the above-mentioned durability test was performed on the glass plate with the low-emissivity laminated film. Next, under the above-mentioned conditions for measuring the spectral reflectance spectrum, the L1 * Value, a1 * Value and b1 * The obtained L1 value was * Value, a1* Value and b1 * value and the above-mentioned L0 * Value, a0 * Value and b0 * Using the values, the change in color of the reflected light ΔE is calculated based on the above equations (1) to (4). * was calculated.
[0105] [Arithmetic mean surface roughness Ra] The arithmetic mean roughness Ra of the surface of the ZrO2-containing layer (or transparent conductive layer) of the glass plate with the low-emissivity laminated film was evaluated by the following method. First, the surface shape of the ZrO2-containing layer was measured using a scanning probe microscope (SPA-400 model, manufactured by SII-NT Co., Ltd.). Three straight lines that intersect with each other within the field of view were selected, and the arithmetic mean roughness was obtained for each of the cross-sectional curves of these straight lines. The arithmetic mean of the obtained values was specified as the arithmetic mean roughness Ra of the surface of the ZrO2-containing layer.
[0106] [Table 1]
[0107] As can be seen from Table 1, the glass plates with low-emissivity laminated films of Examples 1 to 7, in which the arithmetic mean roughness Ra of the surface of the ZrO2-containing layer is 12 nm or less and is smaller than the arithmetic mean roughness Ra of the surface of the transparent conductive layer (15.1 nm: Comparative Example 3), were excellent in surface antifouling properties and scratch resistance. Furthermore, from the results of Examples 1 to 7 and Comparative Examples 1 and 2, it can be seen that the higher the ZrO2 content in the ZrO2-containing layer, the smaller the change in color of reflected light, ΔE * It can be seen that the ZrO2 content in the ZrO2-containing layer was low and the alkali resistance was insufficient in Comparative Examples 1 and 2. [Industrial Applicability]
[0108] The glass sheet with a low emissivity laminated film of the present invention is suitable for glass products such as double glazing units and laminated glass.
Claims
1. A glass plate and A low emissivity laminate film supported on the glass plate; Equipped with The low-emissivity laminated film is a ZrO 2 The glass plate and the ZrO 2 a transparent conductive layer disposed between the containing layer and the conductive layer; The ZrO 2 ZrO in the containing layer 2 The content of is 8 mol% or more and 100 mol% or less, The ZrO 2 SiO in the containing layer 2 The content of is 0 mol% or more and 92 mol% or less, The ZrO 2 A glass plate with a low-emissivity laminated film, wherein the arithmetic mean roughness Ra of the surface of the inclusion layer is 12 nm or less and is smaller than the arithmetic mean roughness Ra of the surface of the transparent conductive layer.
2. 2. The glass plate with a low emissivity laminate according to claim 1, wherein the arithmetic mean roughness Ra of the surface of the transparent conductive layer is 14 nm or more.
3. 3. The glass plate with the low emissivity laminated film according to claim 1, wherein the transparent conductive layer is substantially made of fluorine-containing tin oxide.
4. 3. The glass plate with a low emissivity laminated film according to claim 1, wherein the transparent conductive layer is a layer consisting essentially of fluorine-containing tin oxide and having a thickness of 200 nm or more and 400 nm or less.
5. 3. The glass plate with a low emissivity laminated film according to claim 1, wherein the transparent conductive layer is a layer consisting essentially of fluorine-containing tin oxide and having a thickness of 400 nm or more and 800 nm or less.
6. The transparent conductive layer is a first transparent conductive layer consisting essentially of antimony-containing tin oxide and having a thickness of 100 nm or more and 300 nm or less; 3. The glass plate with the low emissivity laminated film according to claim 1 or 2, further comprising: a second transparent conductive layer substantially consisting of fluorine-containing tin oxide and having a thickness of 150 nm or more and 400 nm or less.
7. The low-emissivity laminated film-attached glass plate according to any one of claims 1 to 6, wherein the low-emissivity laminated film further comprises a base layer disposed between the glass plate and the transparent conductive layer.
8. 8. The glass plate with a low emissivity laminated film according to claim 7, wherein the underlayer is a layer containing silicon oxycarbide as a main component and having a thickness of 20 nm or more and 120 nm or less.
9. The undercoat layer is a first underlayer consisting essentially of tin oxide and having a thickness of 10 nm or more and 90 nm or less; Substantially SiO 2 8. The glass plate with a low emissivity laminated film according to claim 7, further comprising a second underlayer having a thickness of 10 nm or more and 90 nm or less.
10. The undercoat layer is Substantially SiO 2 a first underlayer having a thickness of 10 nm or more and 30 nm or less; a second underlayer consisting essentially of tin oxide and having a thickness of 10 nm or more and 90 nm or less; Substantially SiO 2 and a third underlayer having a thickness of 10 nm or more and 90 nm or less. The glass plate with a low emissivity laminated film according to claim 7 .
11. The ZrO 2 The glass plate with a low emissivity laminate according to any one of claims 1 to 10, wherein the inclusion layer has a physical film thickness of 15 nm or more and 150 nm or less.
12. The ZrO 2 The glass plate with a low emissivity laminated film according to any one of claims 1 to 11, wherein the inclusion layer has a physical film thickness of 30 nm or more and 150 nm or less.
13. A glass product that is used as a skylight in a building to separate an indoor space from an outdoor space, The glass product comprises: a glass plate with a low-emissivity laminate film according to any one of claims 1 to 12; and a second glass plate facing the glass plate with a low-emissivity laminate film via an air gap layer; A glass product, in which the low-emissivity laminated film included in the low-emissivity laminated film-coated glass plate is in contact with the outdoor space.
14. 14. The glass article of claim 13, further comprising a low-emissivity film supported on the second glass sheet and in contact with the air gap layer.
15. The glass product according to claim 14, wherein the low-emissivity film has a layer containing Ag as a main component.
16. 16. The glass product according to claim 15, wherein the low-emissivity film has two of the layers containing Ag as a main component.
17. A glass product that is used as a window in a building to separate an indoor space from an outdoor space, The glass product comprises: a glass plate with a low-emissivity laminate film according to any one of claims 1 to 12; and a second glass plate facing the glass plate with a low-emissivity laminate film via an air gap layer; A glass product, in which the low-emissivity laminated film included in the low-emissivity laminated film-coated glass plate is in contact with the indoor space.
18. A glass product that is used as a door for a refrigerator or freezer to separate an interior space from an exterior space, The glass product comprises: a glass plate with a low-emissivity laminate film according to any one of claims 1 to 12; and a second glass plate facing the glass plate with a low-emissivity laminate film via an air gap layer; The low-emissivity laminated film included in the low-emissivity laminated film-attached glass plate is in contact with the outside space, Glass products.
19. A glass product used as a skylight for transportation equipment to separate the interior space from the exterior space, The glass product comprises a glass sheet with a low emissivity laminated film according to any one of claims 1 to 12, A glass product, wherein the low-emissivity laminated film included in the low-emissivity laminated film-coated glass plate is in contact with the interior space of the aircraft.
20. 20. The glass article of claim 19, further comprising a second glass sheet in contact with the exterior space.
21. 20. The glass product according to claim 19, wherein the low emissivity laminated glass sheet further comprises a compressive stress layer formed on both main surfaces of the glass sheet.
Citation Information
Patent Citations
Hydrophilic member
JP2000319543A
Products containing condensation prevention and / or low emissivity coatings and / or methods for manufacturing the same
JP2015504035A
double glazing unit
JP2017537046A
Glass article and manufacturing method therefor
JP2018127366A
Protective layer over a functional coating
WO2019028296A1